Chemical production of materials for thermal insulation, waterproofing and wall construction finishing: Lecture notes in 2 parts - Rudenko Ihor Ihorevych; Konstantynovskyi Oleksandr Petrovych; Berdnyk Oksana Yuriivna (KNUCA, 2025)
Contains the fundamentals of chemical processes in the technologies of materials for thermal insulation, waterproofing and finishing of wall structures. It is intended for students of the speciality 161 "Chemical technology and engineering" the specialisation "New technologies and design of modern wall and finishing materials" of full-time education.
Keywords: Chemical production; waterproofing; wall construction finishing; thermal insulation